Epidemiological study: notified cases of leptospirosis in Curitiba, Paraná, between 2018-2022 (Research, Society and Development, 2023)
Leptospirosis is an infectious zoonosis caused by the bacterium Leptpspira interrogans, transmitted mainly by contact between rodent urine and human mucosa. The manifestations of the disease occur between the 5th and 14th day, causing myalgia, headache, nausea, weakness and loss of appetite. In this context, the objective of this work was to carry out an epidemiological survey of leptospirosis cases occurring in the city of Curitiba-PR between the years 2018 and 2022. The study consisted of a qualitative-quantitative approach, of a basic and exploratory nature, using epidemiological data available in Platform of the Department of Informatics of the Unified Health System of Brazil (Datasus). The following indicators were considered: total incidence of cases, notifications by gender, age group, area of residence and related or not to work activity. There were 1,418 cases of leptospirosis in Paraná, 520 in Curitiba (36.67%), mainly in 2019. There was a prevalence in men, with the most affected age group being adults between 20-59 years and those with lower prevalence individuals younger than 1 year and 1-4 years. Of all cases, 70.38% corresponded to the urban area. Concluding that because it is an emerging disease, it is essential that Primary Health Care (PHC) seek to understand the epidemiological behavior, possible areas of incidence and risk factors, promoting health education and early diagnosis, with a health team prepared to population service.